NEW BORN SCREENING IN PREVENTING CONGENITAL HYPOTHYROIDISM - Ali, Mazahir; Zia, Aisha; Siddiqui, Saad Ebrahim (Journal of Ayub Medical College Abbottabad, 2015)
Congenital Hypothyroidism is one of the most common preventable causes of mental retardation which is highly prevalent in our society due to lack of a national neonatal screening program, lack of education of the parents, increased consanguinity, and lack of suspicion from doctor’s leads to delayed diagnosis and an increased incidence of congenital hypothyroidism in our society. This Menace can be easily tackled with a mass neonatal screening program and effective legislation which would make sure that serious efforts are being made to eradicate this preventable disease from Pakistan.